THE EFFECTS OF ATTITUDE, PERCEIVED BEHAVIOURAL CONTROL, AND SUBJECTIVE NORM ONLINE ON SHOPPING BEHAVIOUR IN NORTH SUMATERA - Endang Sulistya Rini; Beby Karina; Yeni Absah (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
Due to advances in technology, now in – store shopping for our needs is the past; we just stay at home to find our needs. Consumers must have access and knowledge of the internet shop online. Once the infrastructure is ready, the internet can give consumers easy access to information and shopping quickly, 24 hours a day, seven days a week, regardless of their geographic location. The development of shopping through the online system in Indonesia is growing rapidly. Indonesia is becoming one of the trending countries with an online store presence. The emergence of various online stores such as Kaskus, Tokopedia, Bukalapak, Shopee, and Lazada proves the case. The research method used is qualitative - quantitative with descriptive technique. Data collection is questionnaires distributed to 150 people. The results provide empirical evidence that there are significant effects of attitude, perceived behavioural control, and subjective norm variables on online shopping behaviour variable. Keywords: Attitude, Perceived Behavioural Control, Subjective Norm, Online Shopping Behaviour